No overall progression and occasional repair of erosions despite persistent inflammation in adalimumab-treated rheumatoid arthritis patients: results from a longitudinal comparative MRI, ultrasonography, CT and radiography study. Issue 2 (26th October 2010) - Døhn, Uffe Møller; Ejbjerg, Bo; Boonen, Annelies; Hetland, Merete Lund; Hansen, Michael Sejer; Knudsen, Lene Surland; Hansen, Annette; Madsen, Ole Rintek; Hasselquist, Maria; Møller, Jakob M; Østergaard, Mikkel
Abstract : Aim: To monitor joint inflammation and destruction in rheumatoid arthritis (RA) patients receiving adalimumab/methotrexate combination therapy using MRI and ultrasonography. To assess the predictive value of MRI and ultrasonography for erosive progression on CT and compare MRI/ultrasonography/radiography for erosion detection/monitoring. Methods: Fifty-two erosive biological-naive RA patients were followed with repeated MRI/ultrasonography/radiography (0/6/12 months) and clinical/biochemical assessments during adalimumab/methotrexate combination therapy. Results: No overall erosion progression or repair was observed at 6 or 12 months (Wilcoxon; p>0.05), but erosion progressors and regressors were observed using the smallest detectable change cut-off. Scores of MRI synovitis, grey-scale synovitis (GSS) and power Doppler ultrasonography decreased after 6 and 12 months (p<0.05), as did DAS28, HAQ and tender and swollen joint counts (p<0.001). Patients with progression on CT had higher baseline MRI bone oedema scores. The RR for CT progression in bones with versus without baseline MRI bone oedema was 3.8 (95% CI 1.5 to 9.3) and time-integrated MRI bone oedema, power Doppler and GSS scores were higher in bones/joints with CT progression (Mann–Whitney; p<0.05). With CT as the reference method, sensitivities/specificities for erosion in metacarpophalangeal joints were 68%/92%, 44%/95% and 26%/98% for MRI, ultrasonography and radiography, respectively. Median intraobserver correlation coefficient was 0.95 (range 0.44–0.99). Conclusion: During adalimumab/methotrexate combination therapy, no overall erosive progression or repair occurred, whereas repair of individual erosions was documented on MRI, and MRI and ultrasonography synovitis decreased. Inflammation on MRI and ultrasonography, especially MRI bone oedema, was predictive for erosive progression on CT, at bone/joint level and MRI bone oedema also at patient level.